Efeitos de pontos de contato corporal e orientação segmentar na sensibilidade háptica durante o uso do sistema âncora em tarefas de controle postural - Pacheco, Stephanie Cristina Miranda [UNESP] (2014)
An efficient posture control is important insofar as this is critical to the success of most daily activities. The handling of tools allows you to enlarge the haptic information, and attracting invariant instances, physical and perceptual helpful in guiding behavior. This study investigated the effects of different points of body contact and orientation target on postural control tasks using a flexible tool, called anchor system. Twenty-nine blindfolded young adults remained standing in the tandem position on a balance beam supported on a force platform, while maintaining a flexible cable (anchor system) attached to (1) hand (2) wrist (3) elbow stretched and attached to the load cells in contact with the ground and arms directed above and parallel to the body. The non-contact condition was established as a control (CON). The results showed that in comparison with the condition CON anchoring system improves the posture control. Body contact point presented is invariant to body sway. The lateral orientation of the arms (created when an orthogonal direction from the position of the arm and the support base) reduced the levels of body sway. This study corroborated other. From these results we conclude that the anchor system can be a useful tool to stabilize the posture, especially in orthogonal directions to widen the degree of freedom for facilitating the independent control of body posture contact point at which the tool is fixed. Still, its benefits can be inserted in clinical settings rehabilitation